EDUCATION AND HUMANITY - Olugbenga, Michael (jfpublisher, 2022)
The paper focuses on the necessity of education to human existence and its importance to man of any background, culture, race and religion. The paper distinctively discusses education and humanity philosophically, in line with the R S Peters and Robin M. Coupland respectively. It also discusses the challenges stifling the quality and spread of education in Nigeria. These challenges include poor funding, obsolete curriculum, safety of school, politicization of education etc. The paper proffers solutions to challenges ranging from injection of the appropriate amount of fund, constant monitoring of educational actors and disbursement of fund. The paper concludes that education is light to humans and brings one out of the dark and that quality education is necessary in our schools so as to produce innovators, entrepreneurs and critical thinkers. The paper recommended that government should take funding of education seriously, instructional materials and technology should be provided to schools and policies should be formulated to allow education for all.